Ostwald Ripening in an Oxide‐on‐Metal System. Issue 17 (1st May 2022) - Michalak, Natalia; Ossowski, Tomasz; Miłosz, Zygmunt; Prieto, Mauricio J.; Wang, Ying; Werwiński, Mirosław; Babacic, Visnja; Genuzio, Francesca; Vattuone, Luca; Kiejna, Adam; Schmidt, Thomas; Lewandowski, Mikołaj
Abstract: Ostwald ripening is a well‐known physicochemical phenomenon in which smaller particles, characterized by high surface energy, dissolve and feed the bigger ones that are thermodynamically more stable. The effect is commonly observed in solid and liquid solutions, as well as in systems consisting of supported metal clusters or liquid droplets. Here, evidence is provided for the occurrence of Ostwald ripening in an oxide‐on‐metal system which, in this case, consists of ultrathin iron monoxide (FeO) islands grown on Ru(0001) single‐crystal support. The results reveal that the thermally‐driven sintering of islands allows altering their fine structural characteristics, including size, perimeter length, defect density and stoichiometry, which are crucial, for example, from the point of view of heterogeneous catalysis. Abstract : Ostwald ripening is observed in an oxide‐on‐metal system consisting of ultrathin iron monoxide (FeO) islands grown on Ru(0001). High temperature annealing in ultra‐high vacuum leads to islands sintering, change of their stoichiometry, average size and total perimeter length, as well as the number of internal defects and the exposed substrate area.